Use of single particle inductively coupled plasma mass spectrometry for the study of zinc oxide nanoparticles released from fabric face masks. Issue 4 (21st March 2022) - Suwanroek, Wanida; Sumranjit, Jitapa; Wutikhun, Tuksadon; Siripinyanond, Atitaya
Abstract : An analytical method based on single particle inductively coupled plasma mass spectrometry (SP-ICP-MS) was developed to study the release of ZnO nanoparticles from fabric face mask samples upon washing. Abstract : An analytical method based on single particle inductively coupled plasma mass spectrometry (SP-ICP-MS) was developed to study the release of ZnO nanoparticles from fabric face mask samples upon washing. Before application, the method was tested with commercial ZnO nanoparticle powders suspended in various types of dispersing media, including deionized water, detergent, 20% ethanol, and pure ethanol. These dispersing media were representative simulants normally used in migration studies of nanoparticles. The commercial ZnO nanoparticle suspensions were subjected to size analysis by SP-ICP-MS, and the results were in good agreement with those analyzed by transmission electron microscopy (TEM) and dynamic light scattering (DLS). Therefore, a method based on SP-ICP-MS was applied to examine the release of ZnO nanoparticles from four commercial fabric face mask samples upon washing in deionized water and 4% detergent for five washing cycles. The total content of Zn in fabric face mask samples was found to be approximately 60–100 μg g −1, as determined by conventional ICP-MS after acid dissolution of samples. With SP-ICP-MS, the released ZnO nanoparticles from fabric face mask samples upon washing in deionized water and 4% detergent were in the range of 100–200 nm. The released percentage of Zn from mask samples was approximately 0.25–1.17% in the first washing cycle in deionized water. However, higher percentages ranging around 1.97–3.12% were found for the release of Zn from mask samples in 4% detergent. This work illustrates the capability of SP-ICP-MS for providing information that can be useful for quality control of fabric face mask products.